SOME ASPECTS OF PRICE AND PRICE FORMATION FOR PRODUCTS OF MINING INDUSTRIES (Euro-Asia Conferences, 2021)
The selling price of the goods determines the amount of money for which the seller agrees to sell, and the buyer is ready to buy a unit of the produced goods.